Variations in the Number of Different Branches of Basilar Artery in Relation to Different Age Group - Sultana, Anjuman Ara; Ara, Shamim; Rahman, Mushfika; Akhter, Farhana; Khan, Khushruba Rahman (Bangladesh Journal of Anatomy, 2018)
Context: Basilar artery is one of the main arteries that supplies the posterior portion of brain. Anatomy of basilar artery and its branches are very complex and variable. So, detailed morphological knowledge on basilar artery is essential for proper diagnosis and treatment of related neurological disorders. Materials and Methods: A cross-sectional descriptive type of study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka, from January 2010 to December 2010. 70 postmortem basilar arteries with its branches were collected from unclaimed dead bodies and variations in the number of different branches of basilar artery in relation to different age group were observed. Results: The mean ± SD of number of anterior inferior cerebellar artery (AICA) was found 1.94 ± 0.24 in group A, 1.95 ± 0.31 in group B & 2.00 ± 0.00 in group C. The mean ± SD number of labyrinthine artery (LA) was found 1.67 ± 0.59 in group A, 1.74 ± 0.54 in group B & 1.90 ± 0.32 in group C. The mean ± SD number of pontine artery (PA) was found 5.11 ± 1.08 in group A, 5.21 ± 1.14 in group B & 4.80 ± 1.23 in group C. The mean ± SD number of superior cerebellar artery (SCA) was 2.00±0.00 in group A, 2.10 ± 0.30 in group B, & 2.10 ± 0.32 in group C. The mean ± SD number of posterior cerebral artery (PCA) was 2.00 ± 0.00 in group A, 2.00 ± 0.00 in group B & 2.00 ± 0.00 in group C. Conclusion: Statistically non-significant variation was found in the number of different branches of basilar artery in relation to different age group. Bangladesh Journal of Anatomy January 2018, Vol. 16, No. 1, pp. 9-12